Energy saving of variable frequency drive in dust collector fan motors in the smelting process at the steel industry - Turinno, Sarwo; Facta, Mochammad; Cahyadi, Cahyadi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
The dust removal system is a crucial component in the steel industry, designed to eliminate dust and gas generated during the smelting process. Its primary purpose is to prevent personnel in the surrounding area from inhaling harmful dust particles. A dust collector system is used to carry out this process before being removed from the chimney to the outside air. In the operation of the dust collector, there is still limited attention given to optimizing its operation to meet the needs of its load, where the dust collector still operates at maximum capacity continuously when the dust load decreases due to the smelting process, in an idle state. Setting the rotational speed of the fan motor to produce an airflow rate as required using a variable frequency drive (VFD). The Motor speed was varied in low and high conditions at 322 rpm and 879 rpm. The research results showed that the average airflow rate for the speed of 322 rpm was 150,326 m³/h, and it has 384.193 m³/h at the speed of 879 rpm. The energy savings obtained from the application of VFD to control the airflow rate value are 1,253,544 kWh/year, and the cost savings obtained are IDR 1,249,457,447 per year.